2014
DOI: 10.1519/jsc.0b013e3182986d43
|View full text |Cite
|
Sign up to set email alerts
|

Fluid and Electrolyte Balance During Two Different Preseason Training Sessions in Elite Rugby Union Players

Abstract: The purpose of this study was to compare fluid balance between a resistance and an aerobic training sessions, in elite rugby players. It is hypothesized that resistance exercise will result in a higher prevalence of overdrinking, whereas during the aerobic session, underdrinking will be more prevalent. As with previous fluid balance studies, this was an observational study. Twenty-six players completed the resistance training session, and 20 players completed the aerobic training session. All players were memb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
24
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 32 publications
3
24
0
2
Order By: Relevance
“…In this context, Duffield et al (2012) have recently shown that professional Australian football players lost more water when practising high-vs. low-intensity training sessions. In rugby and US football, it was observed that players lost more water while training in high intensity aerobic sessions than in resistance training sessions (Stofan, Osterberg, Horswill, Lacamba, Eichner, Anderson et al, 2007;Cosgrove, Love, Brown, Baker, Howe & Black, 2014). All together, these results confirmed that water loss could depend on duration and nature of the physical activity.…”
Section: Discussionsupporting
confidence: 53%
“…In this context, Duffield et al (2012) have recently shown that professional Australian football players lost more water when practising high-vs. low-intensity training sessions. In rugby and US football, it was observed that players lost more water while training in high intensity aerobic sessions than in resistance training sessions (Stofan, Osterberg, Horswill, Lacamba, Eichner, Anderson et al, 2007;Cosgrove, Love, Brown, Baker, Howe & Black, 2014). All together, these results confirmed that water loss could depend on duration and nature of the physical activity.…”
Section: Discussionsupporting
confidence: 53%
“…Average post-exercise POsm was within the euhydrated threshold (291.50 ± 4.14 mOsmol.kg -1 ) (Kratz et al 2004) Observations demonstrating participants who arrived more hydrated, drank more, and were at a greater risk of diluting their S[Na + ] is consistent with the findings by Jones et al (2015) and Cosgrove et al (2014), who observed rugby union players during training and match play. In the population observed by Jones et al (2015), 94% of players arrived euhydrated and on 36% of the time, players experienced EAH.…”
supporting
confidence: 80%
“…In the population observed by Jones et al (2015), 94% of players arrived euhydrated and on 36% of the time, players experienced EAH. In contrast, for the population observed in Cosgrove et al (2014), 89% of players arrived hypohydrated, and there were no observations of EAH. Interestingly, within the current study, those that commenced exercise in a hypohydrated state were more capable of regulating S[Na + ] as no changes from pre to post were observed within these individuals.…”
mentioning
confidence: 67%
See 2 more Smart Citations